2020
DOI: 10.1038/s41563-020-0621-z
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the conversion mechanism and performance of monodisperse FeF2 nanocrystal cathodes

Abstract: The application of transition metal fluorides as energy dense cathode materials for lithium ion batteries has been hindered by inadequate understanding of their electrochemical capabilities/limitations. Here, we present an ideal system for mechanistic study through the colloidal synthesis of single crystalline, monodisperse iron(II) fluoride nanorods. Near theoretical capacity (570 mA h g −1 ) and extraordinary cycling stability (>90% capacity retention after 50 cycles at C/20) is achieved solely through the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
157
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(163 citation statements)
references
References 48 publications
1
157
0
Order By: Relevance
“…Meanwhile,astable SEI film with constant-thickness can be observed during the whole discharge/charge process (Figure S16), which is favourable for achieving as table cycling performance. [19] Further,e xs itu Raman (Figure 3d)a nd ex situ Fourier transform infrared (FTIR) (Figure 3e)w ere used to capture the surface variation of the 6h-FeP@NC-1 during electrochemical processes by detecting the graphitization degree of carbon materials.T he I D /I G ratio decreased from 0.79 to 0.55 during the sodiation process,d emonstrating the enhanced graphitization degree, [6,20] which may be ascribed to more graphitized carbon layers.While the I D /I G rose to 0.80 during the desodiation process and it was close to the original value, indicating some special effect of the FePn anoparticles is…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile,astable SEI film with constant-thickness can be observed during the whole discharge/charge process (Figure S16), which is favourable for achieving as table cycling performance. [19] Further,e xs itu Raman (Figure 3d)a nd ex situ Fourier transform infrared (FTIR) (Figure 3e)w ere used to capture the surface variation of the 6h-FeP@NC-1 during electrochemical processes by detecting the graphitization degree of carbon materials.T he I D /I G ratio decreased from 0.79 to 0.55 during the sodiation process,d emonstrating the enhanced graphitization degree, [6,20] which may be ascribed to more graphitized carbon layers.While the I D /I G rose to 0.80 during the desodiation process and it was close to the original value, indicating some special effect of the FePn anoparticles is…”
Section: Methodsmentioning
confidence: 99%
“…Another method is to stabilize the interface with Li salt composites [16,17]. Recently, Pasta's group [18] revealed that an in situ-formed cathode solid electrolyte interphase (CEI) layer could significantly improve the cycling stability of FeF 2 nanorods. However, the quality of the CEI layer strongly depends on the composition of the electrolyte and the working conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Conversion-type electrode materials (MX, where M is generally a transition metal ion and X is O, S, F, etc.) have been extensively explored, as they can deliver much higher capacities than intercalation-type materials [1][2][3][4][5][6]. When lithium ions are introduced, MX is converted into M and Li-X via the conversion reaction.…”
Section: Introductionmentioning
confidence: 99%